2022
DOI: 10.3390/su141811635
|View full text |Cite
|
Sign up to set email alerts
|

Post-Industrial Use of Sugarcane Ethanol Vinasse: A Systematic Review

Abstract: Vinasse is a toxic pollutant if it is poured into the ecosystem indiscriminately; despite this, it integrates components that make it valuable in nutrients and water. However, its use has been questioned due to the costs involved in its purification. This systematic review focuses on the valorization of vinasse from the studies performed for its post-industrial use. Trends in vinasse management and bioproduct development were analyzed. The PRISMA statement was used as a formal guide for collecting and analyzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…Filter cake, also known as pressing mud, is a byproduct of the process of clarification and filtration of sugarcane juice after passing through a rotary filter [30]. It is composed of a mixture of ground sediment and crushed sludge, forming an organic compound with a large volume rich in organic matter, containing macronutrients in its composition [30,31]. [30].…”
Section: Filter Cakementioning
confidence: 99%
“…Filter cake, also known as pressing mud, is a byproduct of the process of clarification and filtration of sugarcane juice after passing through a rotary filter [30]. It is composed of a mixture of ground sediment and crushed sludge, forming an organic compound with a large volume rich in organic matter, containing macronutrients in its composition [30,31]. [30].…”
Section: Filter Cakementioning
confidence: 99%
“…This includes furfural, which can be further converted into various chemicals used in petrochemical, plastic, pharmaceutical, and agrochemical industries [60] (Santos et al, 2020). Several studies have revealed the possibility of using alcohol vinasse in the production of biofuels, biomedicine, food, cosmetics, and packaging [61] (Montiel-Rosales et al, 2022). The wax content in filter cakes can meet industrial requirements for use in the food, pharmaceutical, chemical, cosmetic, cleaning, and polishing industries [60] (Santos et al, 2020).…”
Section: Value-added Productsmentioning
confidence: 99%
“…Previous studies have shown positive progress in using cane residues for biorefinery processes, resulting in a wide range of value-added products. However, there are concerns that current technologies may be expensive, slow, and environmentally unfriendly [60,61]. Therefore, intensive research into advanced technologies for bio-based product manufacturing and financial feasibility is essential.…”
Section: Value-added Productsmentioning
confidence: 99%
“…The application of thermophilic anaerobic digestion is a logical choice for the treatment of sugarcane vinasse (industrial wastewater from ethanol production) because this process enables the recovery of energy as hydrogen and methane without requiring energy for heat or interfering in its quality as a bio-fertilizer (Montiel-Rosales et al, 2022;Júnior et al, 2016). In comparison to the single-phase process, Fuess et al (2021) and Yeoh (1997) investigated the thermophilic two-phase anaerobic treatment system of a canemolasses ethanol distillery using bioreactors for acidogenic and methanogenic phases.…”
Section: Anaerobic Treatmentmentioning
confidence: 99%